2021
DOI: 10.1038/s41370-021-00290-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts to Diné activities with the San Juan River after the Gold King Mine Spill

Abstract: Background-On August 5 th , 2015, 3 million gallons of acid mine drainage was accidentally discharged from the Gold King Mine near Silverton, Colorado into Cement Creek which is a tributary of the Animas and San Juan Rivers. The government-initiated risk assessment only assessed a recreational scenario (i.e. hiker drinking from the river), failing to recognize the deep connection of the Diné (Navajo) with the San Juan River.Methods-Utilizing a mixed-methods approach we determined the impacts of the 2015 Gold K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…While dissemination of research results is beginning to grow, there are several groups to turn to for guidance. For example, researchers from Silent Spring have successfully communicated results using digital web-based formats [90], while researchers from the University of Arizona partnered with Community Health Representatives to deliver study results to participants [91]. Engaging youth offers yet another invigorating method to deliver research results, as is the case of researchers from the Center for Environmental Research and Children's Health [92].…”
Section: Data Ownership-collectivementioning
confidence: 99%
“…While dissemination of research results is beginning to grow, there are several groups to turn to for guidance. For example, researchers from Silent Spring have successfully communicated results using digital web-based formats [90], while researchers from the University of Arizona partnered with Community Health Representatives to deliver study results to participants [91]. Engaging youth offers yet another invigorating method to deliver research results, as is the case of researchers from the Center for Environmental Research and Children's Health [92].…”
Section: Data Ownership-collectivementioning
confidence: 99%
“…Further, in contrast with the EPA's conclusion, a later study undertaken by Diné scientists found ongoing detrimental impacts of the spill on the Diné people-encompassing activities associated with diet, livelihood, recreation, and culture (Van Horne et al, 2021).…”
Section: How Epistemic Hubris Can Thwart Meaningful Consideration Of ...mentioning
confidence: 68%
“…To address this oversight, Diné hydrologist Karletta Chief assembled a team of researchers to begin what would become a multiyear study called the Navajo Gold King Mine Exposure Project (Superfund Research Centre, 2020). Focus group data, collected from three Diné farming communities along with the San Juan River, identified 43 unique uses or interactions with the river indicating a far more robust relationship than the limited EPA imaginary of a kayaker or fisherperson (Van Horne et al, 2021). Researchers categorized these uses into five broad categories including livelihood, recreational, cultural and spiritual, dietary, and arts and crafts activities.…”
Section: Case Examplesmentioning
confidence: 99%